A critical review of prominent theories of politeness - Al-Duleimi, Hutheifa Y.; Md Rashid, Sabariah; Abdullah, Ain Nadzimah (Australian International Academic Centre, 2016)
Politeness plays a crucial role in all cultures and societies for maintaining relationships and for face saving. Although politeness is common to all cultures and languages, how it functions and is realised varies from one culture to another. Different theories have been proposed to examine the strategies with which politeness is expressed. Each theory has weak and strong points which may make it appropriate to a culture but not to another. The most widely used of these theories are Brown and Levinson’s (1978) and its modified version (1987), Lakoff’s (1973), and Leech’s (1983, 2005) theories of politeness. This paper aims to provide a critical review of the aforementioned theories. Specifically, it discusses different scholars’ viewpoints on these theories, highlighting the weak and strong points of the theories. Accordingly, it examines the applicability of these theories to the East and West cultures. A review of these theories indicated that they have weak points as well as strong ones. Furthermore, they might not be suitable for all cultures. This confirms that politeness is a social behaviour not specific to one culture or language. Critical review revealed that Leech’s (2005) Grand Strategy of Politeness might be the most applicable theory that could cover aspects of Eastern and Western cultures.